(untitled) (Journal of Medical & Health Sciences Review, 2025)
The high emotional and physical demands placed on mothers who raise children with autism spectrum disorder (ASD) may affect the mothers’ overall health and well-being. A cross-sectional observational research was conducted to examine the association between mothers of children with ASD and their musculoskeletal discomfort and sleep quality. The research, which took place in rehabilitation centers in Lahore, had 118 moms who were main caregivers and ranged in age from 20 to 40. The Sleep Quality Scale (SQS) and the Nordic Musculoskeletal Questionnaire (NMQ) were employed to collect data. At least one musculoskeletal discomfort location, often the neck and upper back, was reported by each participant. More pain is associated with worse sleep, according to a substantial negative correlation between musculoskeletal pain and sleep quality (r = –0.451, p < 0.001). In order to improve the well-being of mothers of children with ASD and the substantial physical and sleep-related challenges they encounter, these findings highlight the necessity of targeted support.